The Impact of Physical Activity on Adolescent Idiopathic Scoliosis - Josipa Glavaš; Mirjana Rumboldt; Željka Karin; Roberta Matković; Vesna Bilić-Kirin; Vesna Buljan; Tanja Obelić-Babok; Jure Aljinović (Life, 2023)
The prevalence of adolescent idiopathic scoliosis (AIS) is increasing, partly due to a lack of physical activity. In a cross-sectional study with 18,216 pupils (5th, 6th, and 8th grades) from four Croatian counties using the forward bend test (FBT; presumed AIS), the prevalence of AIS and its correlation with physical activity were evaluated. Pupils with presumed AIS were less physically active than their peers without scoliosis (p < 0.001). Abnormal FBT was more prevalent among girls than boys (8.3% vs. 3.2%). Boys were more physically active than girls (p < 0.001). Pupils with presumed AIS were less physically active than their peers without scoliosis (p < 0.001). A higher prevalence of presumed AIS was found among inactive or just recreationally active schoolchildren than among those engaged in organized sports (p = 0.001), girls especially. Pupils with presumed AIS were less active and had fewer weekly sports sessions than their peers without scoliosis (p < 0.001). Notably low prevalence of AIS was detected among pupils engaged in soccer (2.8%, p < 0.001), handball (3.4%, p = 0.002), and martial arts (3.9%, p = 0.006), while it was higher than expected in swimming (8.6%, p = 0.012), dancing (7.7%, p = 0.024), and volleyball (8.2%, p = 0.001) participants. No difference was detected for other sports. A positive correlation was found between time spent using handheld electronic devices and the prevalence of scoliosis (rs = 0.06, p < 0.01). This study confirms the increasing prevalence of AIS, particularly among less athletic girls. Further, prospective studies in this field are required to explain whether the higher prevalence of AIS in these sports is due to referral or other aspects.